Aufklärung habsburgisch: Staatsbildung, Wissenskultur und Geschichtspolitik in Zentraleuropa, 1750-1850 - Fillafer, Franz L. (2021)
This book shows that the Enlightenment was many before it became one: The French Revolution reinvented the Enlightenment as a secular-democratic project of modernity and thereby obliterated its eighteenth-century variety. By recovering the rival strands of Enlightenment at play in Habsburg Central Europe and the Empire they produced, Fillafer offers a fresh reading of both.